VARIASI PEMAKAIAN BAHASA JAWA DIALEK REMBANG PADA MASYARAKAT PEDESAAN: KAJIAN SOSIODIALEKTOLOGI - Siti Nur Hasisah; Muhammad Suryadi (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
The focus of this research is on variations in the use of the Javanese dialect of Rembang by rural communities. Research data in the form of written data and oral data. Case study in Tuyuhan Village, Pancur District, Rembang Regency. The objectives of this research are (1) to reveal vocabulary variations and (2) to describe variations in speech level usage. In collecting data, the researcher used the listening method and the speaking method. The results of the study include: (1) there are variations in vocabulary in 11 fields of meaning, namely greeting words/pronouns, animals, plants, clothes, body parts, kinship patterns, work, household equipment, diseases, activities/activities, and natural conditions. (2) there is an influence of Indonesian into Javanese, both Krama and Ngoko